Transformativni pedagoški pristop pri ocenjevanju športne vzgoje - Dobovičnik, Luka (Šport (Ljubljana), 2021)
Many teachers wonder whether it is possible to assess knowledge by it becoming a trigger or a facilitator of learning. The answer to this question can be found in the transformative pedagogical approach. Its purpose is to encourage pupils to research and find solutions to the problems that arise in the acquisition of knowledge, critical thinking, observation and debate and in taking responsibility for their own learning and knowledge and, consequently, also for their assessment. To illustrate, the transformative pedagogical approach is presented through the example of three learning assignments in the class of physical education. Each assignment is analyzed from three aspects of transformative responsibilisation, subjectification and collaboration. This kind of approach does not represent a completely new didactic method, but merely denotes a different, more active preparedness of the pupils to cooperate in the learning process. It also means that a part of the learning process is transferred to the home environment in the form of so-called homework, while the product or other evidence of the pupil's progress can become an important part of the assessment of the pupil's knowledge. It is important that teachers change their conventional ideas of teaching and assessing knowledge since traditional methods of assessment - and with it numerous related errors - are still predominant in classes of physical education.
Keywords: assessment; dokazi; evidence; ocenjevanje; odgovornost; physical education; responsibility; sport; šport; športna vzgoja; transformative judgement; transformativna presoja